AN ANALYSIS OF READING COMPREHENSION IN ENGLISH TEXTBOOKS AT HIGH SCHOOL GRADE XII IN INDONESIA - nisya anizar; Beatrik Nuyen Saragih; Tria Wahyuni Feronika Sinaga (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2019)
AbstractThis study aims to determine the forms of text and the use of appropriate genres focusing on reading comprehension in English textbooks in high school in 12th grade. The form of this research is descriptive by comparing books and analyzing reading texts in the textbook "English Skills for the Future by Grafindo, Let's Learn English by Bailmu, and Pathway to English by Erlangga" for high school class XII which consists of 3 topics on "English Skills for the Future by Grafindo ", 3 topics on" Let's Learn English by Bailmu "and 3 topics in the book" Pathway to English by Erlangga ".Qualitative data is grouped based on indicators. Data obtained through textbook evaluation by looking at the form of text. It was found that in the three textbooks "English Skills for the Future by Grafindo, Let's Learn English by Bailmu, and Pathway to English by Erlangga" have the same genre namely factual genre (descriptive text, explanation, analytical exposition, and report etc). Key Words: Reading Comprehension, Analysis of english textbooks, conformity to the curriculum